Who knows how much? Sociodemographic profile and general knowledge - Urch, Dražen; Huić, Aleksandra; Ljubotina, Damir; Tomiša, Tia; Tonković Grabovac, Maša (2008)
This study examined relative influence of sociodemographic factors on general knowledge. General knowledge was measured using The Advanced Vocabulary Test (words of Latin and Greek origin).The following sociodemographic data was collected: gender, age, degree of education, profession, current work status, average monthly income, town size. Foreign language knowledge as well as whether or not participants learned Latin or Greek during their schooling was also appraised. Total of 600 respondents participated in the study. Results of a hierarchical regression analysis are discussed. Best predictors proved to be degree in higher education and excellent knowledge of English language.
XXIX International Congress of Psychology (20-25.07.2008. ; Berlin, Njemačka)
Projekt MZOS
Projekt MZOS
ENG